Evaluasi Penggunaan Aplikasi Pembelajaran Online Mahasiswa STAI Attanwir Bojonegoro - Khoirul Faizin (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2021)
This study discusses online learning at STAI Attanwir Bojonegoro. In the selection of media or learning applications, it is often difficult for students to understand the material presented so that lessons do not run optimally and effectively. These problems make researchers intrigued to conduct research so that learning can actually be carried out optimally and effectively. In this study, researchers used a qualitative approach with a phenomenological study using 56 respondents from students who were taken randomly. Based on existing data, this study shows that from several applications used in learning, there are two applications that the researchers think are very suitable for use at STAI Attanwir, namely Gogole Zoom and Google Meet.